ANALISIS TINGKAT PENGETAHUAN REMAJA TENTANG PERILAKU MEROKOK DI KOTA DENPASAR - EDI JANUARTHA, IDA BAGUS PUTU (E-Jurnal Matematika, 2012)
The professional of health said smoking is dangerous behavior, because it can make a kind of disease. Although all the people be aware about a dangerous of smoking behavior, but a count of smoker in Indonesian  increase inclined . The purpose of this research was to see the influence of age, the parent level of education, the parent is smoker or no, communication with father, communication with mother, activity with friends, access to media information and intencity to observe advertisement of cigarette to the knowledge level of adolescents about smoking behavior . The method of analysis used in this study is Ordinal Logistic Regression method. Ordinal logistic regression is a statistical method to analyze the response variable (dependent) which has an ordinal scale. The setting of this research that is in SMPN 10 Denpasar, SMP Santo Yoseph Denpasar, SMAN 6 Denpasar  dan SMAK Santo Yoseph Denpasar. That take a sample 144 respondent, 81 respondent is a boys and 63 respondent is a girls. The results showed that the independent variables that significantly affected the knowledge level of adolescents about smoking behavior is age, the parent level of education, the parent is smoker or no, communication with father, activity with friends and intencity to observe advertisement of cigarette with the value of Pseudo R 2 = 0.599.
Keywords: Smoking Behavior; Knowledge; Adolescents; Ordinal Logistic Regression